(untitled) (Clinics, 2011)
OBJECTIVE: After burn injuries, scarred skin lacks elasticity, especially in hypertrophic scars. Topical treatment with tretinoin can improve the appearance and quality of the skin (i.e., texture, distensibility, color, and hydration). The objective of this prospective study was to examine the effects of treatment with 0.05% tretinoin for one year on the biomechanical behavior and histological changes undergone by facial skin with post-burn scarring. Setting: Tertiary, Institutional. METHOD: Fifteen female patients who had suffered partial thickness burns with more than two years of evolution were selected. Skin biopsies were obtained initially and after one year of treatment. The resistance and elastance of these skin biopsies were measured using a mechanical oscillation analysis system. The density of collagen fibers, elastic fibers, and versican were determined using immunohistochemical analysis. RESULTS: Tretinoin treatment significantly lowered skin resistance and elastance, which is a result that indicates higher distensibility of the skin. However, tretinoin treatment did not significantly affect the density of collagen fibers, elastic fibers, or versican. CONCLUSION: Topical tretinoin treatment alters the mechanical behavior of post-burn scarred skin by improving its distensibility and thus leads to improved quality of life for patients.